Upaya Meningkatkan Kemampuan Daya Ingat Menggunakan Media APE Beras pada Kelompok B di TK Muslimat NU 177 - Farida, Jayyidatul; Suwargono, Trio; Triana, Rizki Sevi (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2024)
This study was conducted to improve memory ability using APE Rice media in group B at Muslimat NU 177 Kindergarten, Ampel Village, Wuluhan District. Where there is a problem experienced by group B teachers, namely group B students are able to mention numbers 1 - 10 and are able to mention the letters of the alphabet, but if asked to pour what has been mentioned both numbers and alphabets there are still students who are wrong with the pattern and shape, so researchers are trying to make Educational Game Tools from materials that are easily found, namely rice. Memory ability is the ability to recall information that has been delivered, seen and received. This type of research is a class action research with Suharsimi Arikunto model. The object of this research is group B students of Muslimat NU 177 Kindergarten, Ampel Village, Wuluhan District, totaling 16 children with 7 boys and 9 girls. The assessment instrument in this study used observation sheets and documentation. Before being given action, the researcher made an initial observation / pre-cycle and got an average score of 43.75% (Starting to Develop), then the researcher reflected to carry out further research in cycle I using APE Rice media without color and obtained an average score of 50.25% (Starting to Develop) and increased very significantly to 89% (Developing Very Well) in cycle II action after there was an improvement in media in the form of colored rice.